2020
DOI: 10.3390/min10121114
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Biogeopolymers Using Biochar-Immobilized Spores of Pure- and Co-Cultures of Bacteria

Abstract: A sustainable solution for crack maintenance in geopolymers is necessary if they are to be the future of modern green construction. This study aims to develop self-healing biogeopolymers that could potentially rival bioconcrete. First, a suitable healing agent was selected from Bacillus subtilis, Bacillus sphaericus, and Bacillus megaterium by directly adding their spores in the geopolymers and subsequently exposing them to a precipitation medium for 14 days. Scanning electron microscope with energy-dispersive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The two strains were selected due to their alkali tolerance, spore-forming ability, high potential for precipitating calcite, and non-pathogenicity. In addition, Doctolero et al [22] employed these bacteria and found that co-culturing bacteria significantly enhanced the healing efficiency of the geopolymer mortar.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two strains were selected due to their alkali tolerance, spore-forming ability, high potential for precipitating calcite, and non-pathogenicity. In addition, Doctolero et al [22] employed these bacteria and found that co-culturing bacteria significantly enhanced the healing efficiency of the geopolymer mortar.…”
Section: Methodsmentioning
confidence: 99%
“…Schaeffer-Fulton staining was used to confirm sporulation while spore concentration was measured using a hemocytometer. All samples were utilized immediately to avoid germination [22].…”
Section: Bacterial Culture Maintenance and Spore Induction Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The ascospores were collected using method referenced in [30][31][32] and incubated at 28°C (fungi) or 37°C (bacteria) for 2 ~ 4 days. After spore germination, the spores were transferred to PDA and LB for subsequent molecular biological identi cation after single colony formation.…”
Section: Puri Ed Cultures and Molecular Biology Identi Cationmentioning
confidence: 99%
“…To date, this is only the second work in the Philippines to use indigenous bacteria for MICP. The first paper was published by Doctolero and coworkers [28], which used bacteria from the Philippine National Collection of Microorganisms (University of the Philippines Los Banos)-Bacillus sphaericus (BIOTECH 1272), Bacillus subtilis (BIOTECH 1679), and Bacillus megaterium (BIOTECH 1512)-isolated in the past from Laguna in the northern island of Luzon. These authors used these bacterial species to induce "self-healing" properties in oven-cured biochar-containing geopolymers and successfully sealed cracks having sizes between 0.1 and 0.65 mm via MICP.…”
Section: Introductionmentioning
confidence: 99%